Correlation between pain and MRI findings in TMD patients - Wurm, Matthias; Behrends, Tessa; Wüst, Wolfgang; Wiesmüller, Marco; Wilkerling, André; Neukam, Friedrich Wilhelm; Schlittenbauer, Tilo (Journal of Cranio-Maxillofacial Surgery, 2018)
Introduction: Magnetic resonance imaging has been established as the gold standard for assessment of the temporomandibular joint. Apart from an excellent assessment of the soft tissues it has the advantage not to expose the patient to ionizing radiation. There is a lack of literature concerning the correlation between pain intensity and radiological findings of the temporomandibular joint. Moreover there is the question of whether a progressive degeneration of the cartilaginous components is accompanied by an increasing degeneration of the osseous parts of the mandibular joint and vice versa. Therefore, this study aims at analyzing correlations between pain and radiological findings. Furthermore, the link between osseous and cartilaginous degeneration is studied. Materials and methods: 91 patients who attend our outpatient clinic for temporomandibular disorders are included in this prospective study. Apart from a detailed anamnesis and clinical examination - adapted to the Research Diagnostic Criteria for Temporomandibular Disorders -magnetic resonance imaging of both mandibular joints is performed. Pain intensity is measured using the visual analog scale. To assess and grade the radiological findings a classification system is established. The evaluation of the osseous components is based on the classification of osteoarthritis by Kellgren and Lawrence whereas the rating of the cartilaginous components is adapted to the Research Diagnostic Criteria for Temporomandibular Disorders. Correlations are verified by Spearman-Rho. Results: 83,5% of all patients are female. Most of the time, both sides are affected (47.25%). Women state an average pain of 5.7 (+/- 2.4), men 3.5 (+/- 2.5). 182 discs are examined and assessed with our classification system. Most discs (n = 71) show no pathological changes. The majority of patients show no dislocation (n = 104). The most common forms of dislocation are anterior dislocations (n = 51). The majority of patients show no changes in the osseous component (n = 115). Weak to moderate correlations are found between disc and bone degeneration. Moderate to strong correlations are found between left and right TMJ. Conclusions: The classification system which is designed and applied during the study proves to be a reliable and practical Instrument. A standardized evaluation of pathologies concerning the temporomandibular joint is possible by using this system. Numerous patients attending our outpatient clinic do not show any signs of degenerative dysfunctions in the mandibular joints. Degenerations of the osseous components tend to be connected with degenerations of the cartilaginous components and vice versa. The question remains if in the future new procedures in imaging will be able to record pathologies not yet detected. (c) 2018 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd. All rights reserved.
EVALuna2:35087

Imaging temporomandibular disorders: Reliability of a novel MRI-based scoring system - Willenbrock, Dorina; Lutz, Rainer; Wüst, Wolfgang; Heiß, Rafael; Uder, Michael; Behrends, Tessa; Wurm, Matthias; Kesting, Marco Rainer; Wiesmüller, Marco (Journal of Cranio-Maxillofacial Surgery, 2022)
The aim of this study was to assess the inter- and intrarater reliability of a recently proposed scoring system for temporomandibular disorders (TMD), based upon radiological findings from magnetic resonance imaging (MRI). Patients with clinically suspected uni- or bilateral TMD, and subsequently conducted MRI examination of both temporomandibular joints, were included in this study. MRI data were independently evaluated by two experienced radiologists according to the DLJ scoring system proposed by Wurm et al., which includes assessment of the following categories: articular disk (prefix ‘D’), direction of disk luxation (prefix ‘L’), and osseous joint alterations (prefix ‘J’). 60 patients (49 female and 11 male) were eligible for analysis. No significant differences were found between both observers regarding ‘D’ and ‘L’ scores (p = 0.13 and p = 0.59, respectively). Significant differences were found for the assessment of subtle osseous changes (‘J0’ category: p = 0.041; ‘J1’ category: p = 0.018). Almost perfect intra- and interrater agreements were found for ‘D’ and ‘L’ categories (intrarater and interrater agreements for ‘D’: κ = 0.92 and κ = 0.84, respectively; intrarater and interrater agreements for ‘L’: κ = 0.93 and κ = 0.89, respectively). However, the assessment of ‘J’ categories revealed only moderate interrater agreement (κ = 0.49). The DLJ scoring system based upon MRI findings is feasible for routine clinical TMD assessment, and may help to simplify interdisciplinary communication between radiologists and clinicians.
CRIS-Team Scopus Importer:2022-04-08
Keywords: DLJ score; Magnetic resonance imaging; MRI; Temporomandibular disorder; TMD